Management of necrotizing fasciitis due to a human bite: case report - Elkamch, Hind; Mesbahi, Anas; Brahmi, Achraf; Hafidi, Jawad; Gharib, Noureddine; Abassi, Abdelah; Elmazouz , Samir (International Surgery Journal, 2024)
Human bites, often underestimated, present significant risks of infection, with necrotizing soft tissue infections (NSTIs) posing a severe threat due to their rapid progression. We present a case of a 72-year-old diabetic male with a human bite on his forearm, leading to NSTI. Despite initially superficial symptoms, including fever and localized pain, the condition rapidly deteriorated, necessitating surgical intervention. The patient underwent multiple debridement procedures and antibiotic therapy, resulting in wound healing. Human bites predominantly affect young males and can occur in various anatomical regions. Microbial flora in the oral cavity increases infection risk, with diabetic individuals being particularly vulnerable due to compromised immunity and delayed wound healing. Prompt diagnosis, antibiotic therapy, and surgical intervention are crucial in managing NSTIs, emphasizing the importance of early medical attention and vigilance in human bite injuries to prevent adverse outcomes like sepsis and mortality.